Development of high resolution schemes for unsteady turbomachinery flow - Kwang, Ming Hui. (2008)
The aerodynamic performance of turbomachinery is influenced by unsteady flows around the blade-rows. Unsteady flows can cause structural problem such as blade fatigue due to flutter and aerodynamic instabilities when stall and surge occur. As a result, the accurate predictions of unsteady turbomachinery flows are important and have attracted considerable attention. Due to the complexity of the flow nature involved, many researchers have turned to computational fluid dynamics (CFD) for the prediction and analysis of the unsteady turbomachinery flow.